2012
DOI: 10.1128/jvi.07161-11
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Integrin Receptor-Signaling Genes by Epstein-Barr Virus EBNA 3C via Promoter-Proximal and -Distal Binding Elements

Abstract: b Epstein-Barr virus (EBV) establishes a persistent latent infection in B lymphocytes and is associated with the development of numerous human tumors. Epstein-Barr nuclear antigen 3C (EBNA 3C) is essential for B-cell immortalization, has potent cell cycle deregulation capabilities, and functions as a regulator of both viral-and cellular-gene expression. We performed transcription profiling on EBNA 3C-expressing B cells and identified several chemokines and members of integrin receptor-signaling pathways, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
76
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 58 publications
14
76
2
Order By: Relevance
“…4). RBPJ-independent binding has been noted in prior EBNA3A and EBNA3C ChIP-seq experiments (51,52). This does not appear to be a technical artifact of the RBPJ ChIP-seq, as we did not observe enrichment for RBPJ cognate binding sequences (e.g., GTGGGAA; see further discussion below) at EBNA3A-, EBNA3B-, or EBNA3C-bound sites such as might occur if the RBPJ ChIP was impaired by EBNA3 cobinding.…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclsmentioning
confidence: 52%
See 2 more Smart Citations
“…4). RBPJ-independent binding has been noted in prior EBNA3A and EBNA3C ChIP-seq experiments (51,52). This does not appear to be a technical artifact of the RBPJ ChIP-seq, as we did not observe enrichment for RBPJ cognate binding sequences (e.g., GTGGGAA; see further discussion below) at EBNA3A-, EBNA3B-, or EBNA3C-bound sites such as might occur if the RBPJ ChIP was impaired by EBNA3 cobinding.…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclsmentioning
confidence: 52%
“…As shown in Fig. 8B, EBNA3C binding was observed at all eight of these sites, including the GSG2 site, but not at a site near the PPIA gene, which has been used in previous EBNA3 ChIP studies as a negative control (52). We additionally confirmed IRF4 binding at each of these sites by ChIP, albeit at low levels at the GSG2, ALPK2, and TRIB2 sites, which were nevertheless significantly above those at the PPIA control site (P Ͻ 0.004; two-sample t test).…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclsmentioning
confidence: 93%
See 1 more Smart Citation
“…ChIP-qPCR assays for EBNA-2 were carried out as described previously (19)(20)(21) using chromatin from Daudi/pHEBoMT-EBNA-2 cell lines. Cells at 5 ϫ 10 5 /ml were treated for 24 h with 4 to 10 M cadmium chloride (CdCl 2 ) before chromatin preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that the p53 tumor suppressor is negatively regulated by EBNA3C at both the transcriptional and posttranscriptional levels (16). Critically, EBNA3C has also been shown to regulate the major cell cycle checkpoints (17). Recently, it was suggested that EBV has a potential role in inducing genomic instability and that viral proteins associated with the latency III program can regulate the DNA damage response (DDR) (18).…”
mentioning
confidence: 99%